An Unusual Presentation of Cholecystocolonic Fistula and Subacute Colonic Obstruction - James S. Barnett; Hannah M. Story; Kevin K. Yu; Salem Muayad (Annals of Internal Medicine: Clinical Cases)
A cholecystoenteric fistula is a spontaneous tract formed between an inflamed gallbladder and surrounding gastrointestinal tract. Cholecystoenteric fistulas most commonly occur between the gallbladder and duodenum but can also occur in other areas. We present a case of a 75-year-old man who presented with new-onset constipation. He was found to have a cholecystocolonic fistula identified via magnetic resonance cholangiopancreatography and a 4.2 cm × 3.7 cm × 5.8 cm obstructing gallstone in the sigmoid colon, requiring manual disimpaction under anesthesia. Although rare, cholecystocolonic fistulas should be considered in the differential diagnosis of older persons with intestinal obstructive symptoms.